1997
DOI: 10.1677/joe.0.1520437
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophs but not somatotrophs carry gonadotrophin-releasing hormone receptors: receptor localisation, intracellular calcium, and gonadotrophin and GH release

Abstract: Gonadotrophs are the primary target cells for GnRH in the pituitary. However, during a limited period of neonatal life in the rat, lactotrophs and somatotrophs respond to GnRH as well. Also, in the adults of a number of teleost fishes (e.g. carp, goldfish, and tilapia but not trout), GnRH is a potent GH secretagogue. In studying hypophysiotrophic actions of the two forms of GnRH present in the African catfish (Clarias gariepinus), chicken GnRH-II ([His5,Trp7,TyrK ] GnRH; cGnRH-II) and catfish GnRH ([His5,Asn8]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…GHRH does not show any effect on GH secretion in the eel (Montero et al 1998, Rousseau et al 1999. GnRH stimulates the release of GH in goldfish, common carp and tilapia, but no effect is seen in the trout (Blaise et al 1995), catfish (Bosma et al 1997) or eel (Rousseau et al 1999). TRH induces the release of GH in the goldfish and common carp, but not in the tilapia (Melamed et al 1995) or eel (Rousseau et al 1999).…”
Section: Introductionmentioning
confidence: 80%
“…GHRH does not show any effect on GH secretion in the eel (Montero et al 1998, Rousseau et al 1999. GnRH stimulates the release of GH in goldfish, common carp and tilapia, but no effect is seen in the trout (Blaise et al 1995), catfish (Bosma et al 1997) or eel (Rousseau et al 1999). TRH induces the release of GH in the goldfish and common carp, but not in the tilapia (Melamed et al 1995) or eel (Rousseau et al 1999).…”
Section: Introductionmentioning
confidence: 80%
“…GnRH stimulated GH release in the goldfish [14, 67]and tilapia [9], but not in the catfish [10, 16]or European eel [13]. In our studies on juvenile turbot, we have tested the three forms of GnRH (sbGnRH, sGnRH, cGnRH-II) expressed in recent teleosts (percomorphs) but none of them were active.…”
Section: Discussionmentioning
confidence: 99%
“…GHRH has been reported to stimulate GH release in goldfish [6], rainbow trout [7, 8], tilapia [9]and catfish [10]but had a very low and non-dose-dependent effect in the salmon [11], and no effect in the European eel [12, 13]. Gonadotropin-releasing hormone (GnRH) strongly stimulated GH release in goldfish [14], carp [15], tilapia [9], but not in trout [8], catfish [16], or European eel [13]. TRH activated GH release in goldfish [17], carp [18, 19], but not tilapia [9], or European eel [13].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that gonadotrophs were the only cell type in an African catfish pituitary cell suspension displaying GnRH binding activity [14]. Furthermore, we demonstrated that the effects of both cfGnRH and cGnRH-II on the cytosolic free calcium concentration ([Ca 2ϩ ] i ) in gonadotrophs in vitro are correlated with their potency to induce LH secretion, both in vitro and in vivo [12,14].…”
Section: Introductionmentioning
confidence: 88%